Short-term evaluation of hepatic toxicity of titanium dioxide nanofiber (TDNF). (2nd January 2019) - Bartel, Leah K.; Hunter, Daniel A.; Anderson, Kayla B.; Yau, W.; Wu, Ji; Gato, Worlanyo E.
Abstract: Various in vitro and in vivo studies have shown titanium dioxide nanoparticles (TDNPs) increase the production of reactive oxygen species and change the expression of genes and proteins involved in the inflammatory response and cell division. Although, the cytotoxicity of TDNPs has been shown to be largely dependent on the characteristics of the particles including shape and surface area. This present study investigates the effects of titanium dioxide nanofibers (TDNFs) with a diameter of 300–800 nm, on the histopathology of liver tissue, changes in feed efficiency and liver weights, changes in hepatic gene expression, and serum biochemical parameters in male Sprague-Dawley rats. Male Sprague-Dawley rats were fed concentrations of 0 ppm, 40 ppm, and 60 ppm TDNF by oral gavage for two weeks. Selected inflammatory response, oxidative stress, and regulatory cell cycle genes were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Differences in gene expression compared to the 0 ppm group were observed in genes Gnat3, IghA, IL-1β, p21, p53, and TNF-α. Histopathology, body and liver weights, and feed efficiency showed no significant differences. Albumin levels in all groups were not significantly higher than the reference range while ALT levels for all groups were high compared to the reference value. Currently, the results suggest TDNF does not exhibit significant hepatic toxicity. This may be explained by the rutile crystalline structure of the nanofibers, the lower concentration or the short duration of exposure toxic used during experimentation.